Performing the Imagined Nation Through Female Bodies in The Circus (1936) - Cybanski, Kara (Université d'Ottawa | University of Ottawa, 2022)
This paper will explore Grigori Aleksandrov's 1936 film The Circus, originally produced in Russian as Tsirk, proving that in lieu of being a light-hearted romantic comedy, it is in fact a production intent on controlling not only women's bodies but also the perception of the Soviet nation on a world stage. By analysing the totalitarian Stalinist government and the gender roles it imparts through cinema, this paper will demonstrate that the female body, controlled by overarching patriarchal ideals, is analogous to the nation's control of its people.
Keywords: nation; motherhood; The Circus; Tsirk; Grigori Aleksandrov; woman